2010
DOI: 10.1152/jn.00494.2009
|View full text |Cite
|
Sign up to set email alerts
|

Where Is Your Arm? Variations in Proprioception Across Space and Tasks

Abstract: The sense of limb position is crucial for movement control and environmental interactions. Our understanding of this fundamental proprioceptive process, however, is limited. For example, little is known about the accuracy of arm proprioception: Does it vary with changes in arm configuration, since some peripheral receptors are engaged only when joints move toward extreme angles? Are these variations consistent across different tasks? Does proprioceptive ability change depending on what we try to localize (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
183
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 49 publications
24
183
1
2
Order By: Relevance
“…Recent studies have reported that the proprioceptive position sense is more precise when the perceiver's hand is closer to the body (Wilson, Wong, & Gribble, 2010) or when there is a weak correlation between the degree of error of the perceived fingertip position and the distance from the fingertip to other body parts (head and shoulder) (Fuentes & Bastian, 2010). However, these studies did not report that fingertip position is generally underestimated depending on relative distance from fingertip to other body parts.…”
Section: Influence Of the Change In Elbow Positionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies have reported that the proprioceptive position sense is more precise when the perceiver's hand is closer to the body (Wilson, Wong, & Gribble, 2010) or when there is a weak correlation between the degree of error of the perceived fingertip position and the distance from the fingertip to other body parts (head and shoulder) (Fuentes & Bastian, 2010). However, these studies did not report that fingertip position is generally underestimated depending on relative distance from fingertip to other body parts.…”
Section: Influence Of the Change In Elbow Positionmentioning
confidence: 91%
“…Previous studies, however, have already reported that the end position (e.g., fingertip position or the end position of a fisted hand) is underestimated to some extent in static and no-weight conditions (Fuentes & Bastian, 2010;Longo et al, 2009;McDonnell, Scott, Dickison, Theriault, & Wood, 1989;Wann & Ibrahim, 1992). Humans would have a general tendency to underestimate the end position of the limb, even when it is statically held.…”
Section: Effect Of Loading a Weight When The Limb Is Swungmentioning
confidence: 98%
“…Even a relatively simple task such as the limb-matching task in Dukelow et al [73] requires several different processes or brain structures to be functional: (1) the left cerebral hemisphere must sense the position of the right limb moved by the robot, (2) this proprioceptive information computed must be transferred to right cerebral hemisphere, (3) the right cerebral hemisphere must plan and control the movement of the left limb, (4) the right hemisphere must sense the final position of the left limb, and (5) the two hemispheres must work together to compare the position of both limbs. Further, tests could be developed to separate these factors such as to move the limb to a spatial location temporarily with the robot and then the subject could be asked to replicate this position with the same limb [75].…”
Section: Robots For Upper-limb Sensory Assessmentmentioning
confidence: 99%
“…Moreover, microneurographic studies suggest that cutaneous afferents can potentially encode position information about hand (Edin and Abbs 1991), knee (Edin 2001) and ankle (Aimonetti et al 2007) movements. Cutaneous input may also have a role in biasing position sense at extreme joint positions where the skin is most stretched (Fuentes and Bastian 2010).…”
Section: Position Controlmentioning
confidence: 99%